Antibacterial properties of selenium nanoparticles and their toxicity to Caco-2 cells. (July 2017) - Nguyen, Trang H.D.; Vardhanabhuti, Bongkosh; Lin, Mengshi; Mustapha, Azlin
Abstract: The antibacterial properties of Se NPs were investigated against four foodborne pathogens ( Escherichia coli O157:H7, Staphylococcus aureus, Salmonella, and Listeria monocytogenes ). The cytotoxicity of Se NPs was also studied using the Caco-2 cell line. Se NPs at concentrations of 10 μg/mL or higher exhibited dose-dependent antimicrobial properties against S. aureus, but not on the other three pathogens. Se NPs also exhibited various degrees of toxicity on Caco-2 cells after 24 h of exposure. Cellular shrinkage and irregular shapes of treated bacterial cells indicated that the antimicrobial effects of Se NPs are bacteriostatic, not bactericidal. This is the first study to investigate the antimicrobial activity of Se NPs against important foodborne pathogens. The results of this study demonstrate that Se NPs can be used as an antimicrobial agent to inhibit the growth of S. aureus and can be potentially used for food safety applications. Highlights: Se NPs inhibited Staphylococcus aureus but not the other bacteria tested. Abnormal changes in treated bacterial cell membranes occurred. Caco-2 cells were inhibited, but dose-dependent effects on mitochondrial activities were unclear. Se NPs can be used as an antimicrobial agent with low toxicity to mammalian cells.